Medicinal properties, phytochemistry, and pharmacology of Myristicaceae family: A review - Megawati Megawati, Akhmad Darmawan, Sumi Hudiyono (Journal of Applied Pharmaceutical Science, 2024)
The Myristicaceae family has 500 species, divided into 3 genera: Myristica, Knema, and Horsfieldia. These species are distributed across tropical Asia, Africa, and America. This plant has active ingredients, including polyketides and lignans, which have a range of biological properties such as anti-inflammatory, anti-cancer, and anti-microbial. This review aims to examine the variety of biological activities and chemical structures of the bioactive chemicals present in the Myristicaceae family from across the globe.
Keywords: Myristicaceae, Myristica, Knema and Horsfieldia, bioactivities